KARAKTERISTIK BURUH WANITA PENYADAP KARET SERTA FAKTOR-FAKTOR YANG MEMPENGARUHI PENDAPATAN RUMAH TANGGANYA (Studi Kasus Di PTPN IX Kebun Balong/Beji-Kalitelo Afdeling Ngandong Kabupaten Jepara) - Malihatin Munawaroh; Shofia Nur Awami (Universitas Wahid Hasyim, 2015)
The number of women who participate as labor in the various social life fields was increasing. The role of women in agriculture also contributed for the improvement of the family economy. This study aimed to determine characteristics of the role of women labor rubber tappers in PTPN IX Balong Beji Plantation and the factors that affect women labor rubber tappers household income. The conclusion of the research illustrated the role of women labor rubber tappers in PTPN IX Balong Beji Plantation run three roles at once: the role of productive, reproductive and social. The factors that affect labor household income is a rubber tappers working period, number of children, marital status and type of husband work. Keywords: Family income, rubber tappers labor, women.